Principais correntes de estudo da criatividade e suas relações com o esporte - Dietmar Martin Samulski; Franco Noce; Varley Teoldo Da Costa (Universidade Federal do Rio Grande do Sul, 2001)
This study aims to present the different approaches about creativity and its correlations with sport. The mystical, pragmatic, psychodynamic, cognitive, psychometric, and social view of creativity as well as your main concepts and visions are presented systematically aiming to correlate them with the sport phenomenon. The new trends about the paradigms that involve the present study of creativity are approached also.